Evasão nos cursos superiores da região norte e estudo comparativo para avaliação das IFES tocantinenses - Franco, Luciano Correia (Universidade Federal do Tocantins, 2016)
In recent decades, education has been changed mainly in Brazil. In higher education, the expansion of educational institutions, public and private, and the increasing number of vacancies were due to educational programs implemented by public policies of higher education nationwide. This new reality, characterized by the existence of various social programs, created conditions for the students without graduation perspective could have access to higher education. It is because of developmental needs of the Government, towards citizen’s formation in front of a global scenario of competitiveness and internationalization of markets. However, for the educational programs being effective, the politics also need to be evaluated and remodeled when necessary. Educational indicators are very useful in the evaluation’s processes of public policies and are widely used for this purpose in Brazil. This paper presents evasion indicators of higher education in the North Region of Brazil, among others, grouped by states from Federation, and administrative categories. These indicators were collected from the microdata of Higher Education census, extracted from INEP during 2010 to 2014. It is used to a comparative study in order to evaluate the performance of Higher Education Federal Institutions operating in the State of Tocantins. The results showed that in the states, in general, the federal category presented better indicators on the evasion that the other administrative categories. Among the federal institutions, the State of Tocantins had the fourth best evasion rate. Comparing the administrative categories within the State of Tocantins, the federal institutions performed well, achieving the best average rate of annual evasion in the period.